2013 IEEE 54th Annual Symposium on Foundations of Computer Science 2013
DOI: 10.1109/focs.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Fully Dynamic (1+ e)-Approximate Matchings

Abstract: We present the first data structures that maintain near optimal maximum cardinality and maximum weighted matchings on sparse graphs in sublinear time per update. Our main result is a data structure that maintains a (1 + ǫ) approximation of maximum matching under edge insertions/deletions in worst case O( √ mǫ −2 ) time per update. This improves the 3/2 approximation given in [Neiman, Solomon,STOC 2013] which runs in similar time. The result is based on two ideas. The first is to re-run a static algorithm after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
145
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 21 publications
(34 reference statements)
0
145
0
Order By: Relevance
“…In fact, our approximation guarantee almost matches the best (2-approximation) one provided by a randomized algorithm [2]. 2 Our algorithm for Theorem 1.1 is obtained by combining previous techniques [5,7,15] with two new ideas that concern fractional matchings. First, we dynamize the degree splitting process previously used in the parallel and distributed algorithms literature [9] and use it to reduce the size of the support of the fractional matching maintained by the algorithm of [5].…”
Section: Designing a Deterministic Polylogarithmic Time Algorithm Witmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, our approximation guarantee almost matches the best (2-approximation) one provided by a randomized algorithm [2]. 2 Our algorithm for Theorem 1.1 is obtained by combining previous techniques [5,7,15] with two new ideas that concern fractional matchings. First, we dynamize the degree splitting process previously used in the parallel and distributed algorithms literature [9] and use it to reduce the size of the support of the fractional matching maintained by the algorithm of [5].…”
Section: Designing a Deterministic Polylogarithmic Time Algorithm Witmentioning
confidence: 99%
“…First, we dynamize the degree splitting process previously used in the parallel and distributed algorithms literature [9] and use it to reduce the size of the support of the fractional matching maintained by the algorithm of [5]. This helps us maintain an approximate integral matching cheaply using the result in [7]. This idea alone already leads to a (3 + ε)-approximation deterministic algorithm.…”
Section: Designing a Deterministic Polylogarithmic Time Algorithm Witmentioning
confidence: 99%
See 1 more Smart Citation
“…One, therefore, asks which static problems solvable in time f(m) can be fully "dynamized", in the sense of having dynamic algorithms that support updates in O(f(m) / m) time. This question has been answered affirmatively for many fundamental graph problems including connectivity (e.g., [30,33,34,52]), reachability [32], shortest paths (e.g., [8,18,31]), and maximum matching [9,27,49].…”
Section: Facing Velocity: Algorithms For Dynamic Big Datamentioning
confidence: 99%
“…Baswana et al [7] provide a randomized 2-approximation in O(log n) amortized time. For deterministic algorithms, Gupta and Peng [17] gave a (1 + ε)-approximation in O( √ m/ε 2 ) worst-case update time. Bhattacharya et al [9] showed a deterministic (4 + ε)-approximation in O(m 1/3 /ε 2 ) worst-case update time.…”
Section: Related Workmentioning
confidence: 99%